Health Education About the Early Detection Hearing Disorders Increasing Knowledge And Attitude of Parents Baby Age 0-3 Months - Dwi Y. Astutik; Yuni S. Arief; Iqlima D. Kurnia (Pediomaternal Nursing Journal, 2016)
Introduction: Hearing disorder is one of disable thats difficult to know early for that requires an examination method is easy and fast so we can know that abnormality earlier. Health education for empowering people about health importance of hearing, do early detection and eradicate hearing disorder can improving health of hearing for Indonesia making quality. Method: The aim of this study was to analyze effect of health education about early detection of hearing disorder program to improvement of knowledge and attitude of parent baby on audiologi poly RSUD Dr. Soetomo Surabaya. This research used preexperimental with pre-post test design. The population were parents baby with age 0-3 mounth who their children in audiologi poly. The sample were 15 respondents who met the inclusion and eksklusion criteria, sample were taken by using konsekutif sampling. The independent variable was health education and the dependent variable was knowledge and attitude, the data was collected using questionnaire, then analized using wilcoxon signed rank test with significant level α ≤ 0,05. Result and Analysis: The result reveals that was effect of health awareness contained on knowledge with significant p=0,015 and was not effect of health awareness contained on attitude with significant p= 0,157 Discussion: It can be concluded that was effect from health education about early detection of hearing disorder to change of knowledge by parent baby so health education must given. Further studies should measure the effect of health with audio-visual method